Impact of product costing for branding and business support on small and medium enterprises in Malaysia - Faizal, Diana Rose; Mohd Ashhari, Zariyawati; Kamarohim, Nor Azlina; Md Nassir, Annuar (Universiti Putra Malaysia Press, 2019)
This study examines the relationship between costing towards branding and business support on Small and Medium Enterprises (SMEs) of food and beverages (F&B) products supplying a hypermarket in Malaysia. Specifically, this study examines the mediating effect of branding on the relationship between products' costing and SMEs' product value. This study also examines the moderating effect of business support on the relationship of products' costing to branding. This study used a quantitative method by distributing questionnaires to SMEs with an F&B background. Four hundred questionnaires were collected from the SMEs. A theory, like transaction cost and the resource-based view, was applied to support the proposed five relationships and hypotheses. This study used partial least squares structural equation modelling (PLS-SEM). The results of this study show that cost is significant with mass-produced SMEs' product value. The result reveals a strong interaction of mediation in the implementation of branding for the SMEs' product value. In brief, business support acting as a moderator has no moderating effect on branding. Therefore, SMEs need to put aside a significant sum of funds to enhance their products' branding. This can help SMEs in manufacturing products according to the demands of consumers and the hypermarket. These actions can increase SMEs' income and contribute to national economic growth.